2009
DOI: 10.1109/jlt.2009.2025148
|View full text |Cite
|
Sign up to set email alerts
|

Maximum-Likelihood Sequence Estimation for Optical Phase-Shift Keyed Modulation Formats

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…Τhis feature can be justified by noting that the constructive output port is resembles a duobinary (DB) signal, while the destructive output port resembles an alternatingmark-inversion (AMI) signal [27,28]. The intrinsic high tolerance of the DB modulation format in chromatic dispersion originates from its narrow spectrum [29] and can explain the better performance of every equalizer when the constructive, rather than the destructive, port (of each channel) is maintained to undergo the process of equalization [30]. Figure 9.…”
Section: Optical Layer Simulationmentioning
confidence: 99%
“…Τhis feature can be justified by noting that the constructive output port is resembles a duobinary (DB) signal, while the destructive output port resembles an alternatingmark-inversion (AMI) signal [27,28]. The intrinsic high tolerance of the DB modulation format in chromatic dispersion originates from its narrow spectrum [29] and can explain the better performance of every equalizer when the constructive, rather than the destructive, port (of each channel) is maintained to undergo the process of equalization [30]. Figure 9.…”
Section: Optical Layer Simulationmentioning
confidence: 99%
“…As a result, MLSE has been commercially available for a number of years [3]. However, in [1,4,5] it has been demonstrated that neither of the two techniques is capable of compensating the residual CD in D(Q)PSK modulated signals. Hence, in [6] the principle of joint-MLSE was proposed as an alternative structure of conventional MLSE for D(Q)PSK modulated signals.…”
Section: Equalization For Direct-detection Receiversmentioning
confidence: 99%
“…Joint-MLSE is based on having more than one input to the MLSE representing the same signal, and then using a joint probability on the input signals it can provide a better estimation of the received signal. In [5], we experimentally evaluated the performance of the joint-MLSE technique and we proved its potential to significantly enhance the tolerance of the direct-detection receiver against CD. However, a major drawback for joint-MLSE is the need to use double as much ADCs, as well as the extra memory locations for storing the histograms of the extra input signals.…”
Section: Equalization For Direct-detection Receiversmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it monitors the phase detuning in a DLI used for PSK signal demodulation. This is particularly true for the cases replacing inline dispersion compensation with electrical equalization [14] , in which the signal is severely distorted by a large accumulated CD, resulting in the failure of other monitoring schemes based on waveforms [12] . In practice, we inserted another PD in front of the DLI to detect the power fluctuation and used the ratio of these two PD outputs to cancel out the effect of the power fluctuation.…”
mentioning
confidence: 99%